2019
DOI: 10.1142/s0219455419500615
|View full text |Cite
|
Sign up to set email alerts
|

Flutter of Telescopic Span Morphing Wings

Abstract: This paper studies the aeroelastic behavior of telescopic, multi-segment, span morphing wings. The wing is modeled as a linear, multi-segment, stepped, cantilever Euler–Bernoulli beam. It consists of three segments along the axis and each segment has different geometric, mechanical, and inertial properties. The aeroelastic analysis takes into account spanwise out-of-plane bending and torsion only, for which the corresponding shape functions are derived and validated. The use of shape functions allows represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Flutter behavior of Goland wing at 50% extension is analyzed and validated with study from literature [3]. In this configuration, the wing span extends by 50%, thus the semi-span length becomes 9.144 m. A schematic view of the wing at 50% extension is illustrated in Figure 4.…”
Section: Goland Wing At 50% Span Extensionmentioning
confidence: 87%
See 2 more Smart Citations
“…Flutter behavior of Goland wing at 50% extension is analyzed and validated with study from literature [3]. In this configuration, the wing span extends by 50%, thus the semi-span length becomes 9.144 m. A schematic view of the wing at 50% extension is illustrated in Figure 4.…”
Section: Goland Wing At 50% Span Extensionmentioning
confidence: 87%
“…Ajaj et al [3] reported the flutter speed of Goland wing at 50% extension is at around 100 m/s. In the current study, the flutter speed is found as 104.1 m/s with the error 3.93%.…”
Section: Goland Wing At 50% Span Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variable wingspan combines the benefits of both large and small wingspans into a single aircraft, making span morphing an emerging technology that is attractive for multi-mission UAVs. Studies in the literature have adopted span morphing for enhanced flight performance, roll control, and flutter suppression [40,41]. Variable wingspan technologies are usually associated with large changes in the inertia, elastic and aerodynamic forces.…”
Section: Spanmentioning
confidence: 99%
“…Based on a lowfidelity aeroelastic model and cantilever uniform morphing wings, the feasibility of active flutter suppression by using morphing device was studied by Ajaj and Friswell. 11 Investigation was also extended into the dynamic behaviour and stability of an axially morphing wing in supersonic airflow 12 to demonstrate that a proposed morphing law is effective for flutter suppression.…”
Section: Introductionmentioning
confidence: 99%